Selective production of methoxyphenols from dihydroxybenzenes on alkali metal ion-loaded MgO - Vijayaraj, Munusamy; Gopinath, Chinnakonda S. (Journal of Catalysis, 2006)
Selective O-methylation of dihydroxybenzenes (DHBs; catechol, resorcinol, and hydroquinone) to methoxyphenols (MPs) was carried out with dimethylcarbonate on MgO and alkali metal ion (Li, K, and Cs)-loaded MgO between 523 and 603 K. Catalytic activity and product selectivity varied with respect to DHB substrates. Selectivity for O-methylated products increased with increasing basicity of alkali ions; however, K-MgO showed high and stable activity toward MPs. Selectivity for MPs obtained from three substrates increased in the following order: catechol < resorcinol < hydroquinone. The mode of interaction of substrates on the catalysts surface influenced reactivity and product selectivity. It is likely that the low reaction temperatures used (< 603 K) kinetically control and favor high MP selectivity from DHBs. Calcined and spent catalysts were characterized by XRD, surface area, SEM, thermal analysis, NMR, and XPS. XRD analysis revealed the formation of alkali oxide phases on alkali-loaded MgO. Crystallite size and surface area of the catalysts decreased after methylation reactions, except on K-MgO. TGA showed 4060 wt% coke deposition on spent catalysts. TGA in N-2 followed by air and C-13 CP-MAS NMR measurements indicated the nature of deposited carbon to be molecular species, graphite, MgCO3 and polyaromatics. XPS revealed the nature and availability of active sites on the spent catalysts, as well as the same changes with reaction conditions and correlated with catalytic activity. (c) 2006 Elsevier Inc. All rights reserved.
Keywords: alkali-loaded MgO; dihydroxybenzene; K-MgO; methoxyphenol; MgO; O-methylation; thermal analysis; XPS